Hubungan Perilaku Penggunaan Insektisida dengan Status Kerentanan Nyamuk Aedes aegypti di Daerah Endemis Kabupaten Purbalingga - Slamet Riyadi; Tri Baskoro Tunggul Satoto (Berita Kedokteran Masyarakat (BKM), 2017)
Insecticide use and Aedes aegypti susceptibility status in endemic areas of PurbalinggaPurpose: This study aimed to identify the correlation between behavior towards insecticide use and susceptibility status of Aedes aegypti mosquito and to identify the level of mosquito susceptibility from an endemic area in Purbalingga.Methods: This research used a cross-sectional design and was conducted from January 2017 until April 2017 in four endemic villages of Purbalingga. 40 respondents were involved in the research. Samples from each village were taken using purposive sampling. Ovitraps were installed and interviews were conducted using questionnaires for selected households. Mosquito susceptibility status was described based on the results of WHO’s standardized bioassay test.Results: The results of susceptibility test indicated that Aedes aegypti from three endemic villages (Purbalingga Lor, Penaruban, Sempor Lor) were resistant, while mosquitoes from Kembaran Kulon Village were tolerant to cypermethrin 0.05%. Variables correlated with susceptibility status of Aedes aegypti mosquito were respondent's negative attitude (PR = 0.55; 0.37 - 0.80) and behavior towards insecticide use (PR = 1.24; 1.05 - 1.47).Conclusions: Misuse of insecticides increased susceptibility status of Aedes aegypti mosquito and becomes the main risk factor for resistance. It is necessary to rotate the insecticide use for programs and households through different modes of action and to provide public health education about insecticide use, selection of active ingredients, dosage, mode of application and periodic replacement of insecticides.